Clarithromycin-Loaded Ocular Chitosan Nanoparticle: Formulation, Optimization, Characterization, Ocular Irritation, and Antimicrobial Activity - Bin-Jumah, May (Int J Nanomedicine, 2020)
PURPOSE: The topically administered drugs through conventional delivery systems have low bioavailability. Henceforth, the present study was designed to prepare and optimize clarithromycin (CTM)-loaded chitosan nanoparticles (CHNPs) to demonstrate the efficacy against microorganisms. METHODS: Clarithromycin-loaded chitosan nanoparticles (CTM-CHNPs) were prepared by ionotropic gelation method. The formulation was optimized by box-Behnken design using the formulation variables like CH (A), STPP concentration (B), and stirring speed (C). Their effects were evaluated on the independent variables like particle size (Y(1)) and entrapment efficiency (Y(2)). Further, CTM-CHNPs were evaluated for physicochemical parameters, in-vitro drug release, ex-vivo permeation, bioadhesive study, corneal hydration, histopathology, HET-CAM, and antibacterial study. RESULTS: The optimized formulation (CTM-CHNPopt) showed the low particle size (152±5 nm), which is desirable for ocular delivery. It also showed high encapsulation (70.05%), zeta potential (+35.2 mV), and was found in a spherical shape. The drug release study revealed a sustained drug release profile (82.98±3.5% in 12 hours) with Korsmeyer peppas kinetic (R(2)=0.996) release model. It showed a 2.7-fold higher corneal permeation than CTM-solution. CHNPs did not exhibit any sign of damage to excised goat cornea, which is confirmed by hydration, histopathology, and HET-CAM test. It exhibited significant (P<0.05) higher antibacterial susceptibility than CTM-solution. CONCLUSION: The finding of the study concluded that CTM-CHNPs can be used for effective management of bacterial conjunctivitis by increasing the precorneal residence time.